The FGV Stock Price Forecasting Using Holt’s Linear Trend and ARIMA Model - Suaaifadawiyah, Rabiatul Adawiyah; Mohd Asrah, Norhaidah (Enhanced Knowledge in Sciences and Technology, 2023)
The focus of this study of analyzing the stock price performance of the largest company that produces palm oil which is Felda Global Venture (FGV) Holding Berhad. There are three main objectives of this study as to analyze the FGV Holding Bhd daily stock price by using the ARIMA model and Holt’s Linear Trend method, to compare the forecasting accuracy between methods and to forecast the FGV Holding Bhd stock price by using the best forecasting model. Generally, the purpose of this study is to analyze and forecast the stock price of FGV Holding Berhad by applying two types time series forecasting techniques within seven year, from 2013 until 2020 for forecasting the further period. The result was revealed that the ARIMA (0, 1, 2) was given the smallest forecasting error in predicting FGV stock price with the lowest error in MAE, MAPE, MSE and RMSE compared to Holt’s Linear Trend Method. This study is recommended for applying the advanced forecasting techniques and conducting the sentiment analysis toward the issues that arise nowadays for further analysis purposes due to evaluate the issues that affected the stock price behaviour.